2009
DOI: 10.1093/eurheartj/ehp125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of revascularizing viable myocardium on left ventricular diastolic function in patients with ischaemic cardiomyopathy

Abstract: In patients with ischaemic cardiomyopathy, LV diastolic filling may largely improve after revascularization. Improvement of diastolic dysfunction is related to the amount of viable tissue and it may represent an additional advantage of revascularizing dyssinergic but viable myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
(21 reference statements)
6
25
0
Order By: Relevance
“…In contrast to the highly significant reduction in left atrial early diastolic strain rate after sleep deprivation, there were no significant changes in left atrial systolic strain, systolic strain rate, and late diastolic strain rate. This fits very well to the isolated, small but significant increase in left ventricular relaxation and isovolemic relaxation time, possibly indicating that acute sleep deprivation affected primarily early left ventricular diastole, i.e., the energy-consuming process of diastole, which for example is also affected by myocardial ischemia [13] or changes in afterload [14]. The only finding which does not fit into the picture is the lack of change (not even a trend) in the early diastolic mitral annular velocity (e′), which is currently regarded as one of the best if not the best non-invasive measures of left ventricular relaxation [15].…”
supporting
confidence: 75%
“…In contrast to the highly significant reduction in left atrial early diastolic strain rate after sleep deprivation, there were no significant changes in left atrial systolic strain, systolic strain rate, and late diastolic strain rate. This fits very well to the isolated, small but significant increase in left ventricular relaxation and isovolemic relaxation time, possibly indicating that acute sleep deprivation affected primarily early left ventricular diastole, i.e., the energy-consuming process of diastole, which for example is also affected by myocardial ischemia [13] or changes in afterload [14]. The only finding which does not fit into the picture is the lack of change (not even a trend) in the early diastolic mitral annular velocity (e′), which is currently regarded as one of the best if not the best non-invasive measures of left ventricular relaxation [15].…”
supporting
confidence: 75%
“…21,22 In line with these observations, the present trial documented an improvement in myocardial perfusion and a reduction in myocardial ischemia after intramyocardial bone marrow cell injection. 2 In patients undergoing coronary artery bypass grafting, improvements in myocardial relaxation and filling pressures were reported by Carluccio et al 23 Accordingly, it may be hypothesized that the observed improvements in myocardial relaxation and, subsequently, filling pressures, are secondary to enhanced myocardial perfusion. From a mechanistic point of view, the current data support this hypothesis because the enhanced myocardial perfusion would be expected to improve active processes such as myocardial relaxation rather than altering myocardial structure and ventricular compliance.…”
Section: Discussionmentioning
confidence: 92%
“…The FAs are the main source of energy for the heart, and L -carnitine transfers the FA across mitochondrial membranes to produce energy [1]. In the literature, it is well established that CABG surgery produces an increase up to 10% in the LVEF value, with improvement of the left ventricular systolic function [23,24]. …”
Section: Discussionmentioning
confidence: 99%